Nona Fernández's Mapocho: Spirits in a Material Wasteland - Resha S Cardone (Studies in 20th & 21st Century Literature, 2015)
This analysis of Mapocho (2002), a novel by Chilean writer and performer Nona Fernández, explores the significance of the author’s environmentalist representation of Chilean history as the accumulation of spiritual and material contaminants—ghosts and trash—that the victorious from throughout the country’s history have attempted to erase to further various economic and political agendas, particularly the neoliberal model installed during the Pinochet dictatorship. Fernández’s depiction of Chile as an ecological and spiritual wasteland in which the female protagonist (re)collects, recycles and reuses the specters and detritus of past conflicts represents the author’s own literary project of advocating for human rights and environmental justice during the Chilean transition while modeling a way to counter the collective amnesia promoted under the newly established democracy.
Keywords: Generation of 1990; Nona Fernández; Mapocho; Chilean literature; neoliberalism in Chile